2017
DOI: 10.1002/2016ja023495
|View full text |Cite
|
Sign up to set email alerts
|

MAVEN observations of the solar cycle 24 space weather conditions at Mars

Abstract: The Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft has been continuously observing the variability of solar soft X‐rays and EUV irradiance, monitoring the upstream solar wind and interplanetary magnetic field conditions and measuring the fluxes of solar energetic ions and electrons since its arrival to Mars. In this paper, we provide a comprehensive overview of the space weather events observed during the first ∼1.9 years of the science mission, which includes the description of the solar and helios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 98 publications
(155 citation statements)
references
References 74 publications
8
143
0
Order By: Relevance
“…Moreover, the largest nightside densities recorded by MAVEN have been observed at high northern altitudes during this time period coincidently with a major solar energetic particle event (Lee et al, 2017). First period: electron depletions have equally been observed on the duskside and on the dawnside.…”
Section: Detail Of Each Time Periodmentioning
confidence: 70%
“…Moreover, the largest nightside densities recorded by MAVEN have been observed at high northern altitudes during this time period coincidently with a major solar energetic particle event (Lee et al, 2017). First period: electron depletions have equally been observed on the duskside and on the dawnside.…”
Section: Detail Of Each Time Periodmentioning
confidence: 70%
“…The CIR associated with the coronal hole triggered a moderate geomagnetic storm on 7 June 2015, and a minor geomagnetic storm on 4 July 2015 at Earth . Lee et al (2017) observed that the IMF configuration fluctuated between Parker spiral configuration and radial configuration, upon crossing the heliospheric current sheet associated with the HSS. In this study, we present the observations only for the June 2015 event.…”
Section: Observationsmentioning
confidence: 99%
“…The images of coronal hole in May, June, and July are shown in Figure 7 of Lee et al (2017). The images of coronal hole in May, June, and July are shown in Figure 7 of Lee et al (2017).…”
Section: Observationsmentioning
confidence: 99%
“…Throughout this period the EUV irradiance at Mars changed by a factor of about 2, primarily owing to the varying Mars‐Sun distance rather than solar cycle variability. The EUV irradiance was highest during the beginning of the mission, when Mars was near perihelion [ Bougher et al , ; Lee et al , ].…”
Section: Ngims Data Descriptionmentioning
confidence: 99%
“…Alternatively, a more plausible explanation may be that the larger nightside densities were the result of a period of enhanced particle precipitation. The first period of observations covered the full month of December 2014, during which the MAVEN Solar Energetic Particle (SEP) instrument [ Larson et al , ] detected an extended event of energetic electron fluxes [ Lee et al , ]. These energetic electrons are expected to produce significant ionization at these altitudes [e.g., Sheel et al , ] and MARSIS observations show that nightside densities are enhanced during SEP events [ Němec et al , ].…”
Section: Variabilitymentioning
confidence: 99%